Nonrecursive control design for nonlinear systems : theory and applications - Zhang, Chuanlin, 1986-; Yang, Jun, 1984- (CRC Press, 2023)
"Based on the authors' recent advances, this book focuses on a class of nonlinear systems with mismatched uncertainties/disturbances and discusses their typical control problems. It aims to provide a comprehensive view of the non-recursive control theory and application guidelines. Various applications on the non-recursive synthesis of complex nonlinear systems not only greatly simplify the control design process, weaken the system assumptions, and reduce the conservatism of gain selection, but also realize the essential detachment of control law design and Lyapunov function-based stability analysis. Therefore, different from the classical recursive control design methods, it is of significance to study the synthesis of nonlinear systems from the perspective of a new non-recursive control framework. This book discusses the following typical control problems: theoretical background, homogeneous systems theory review, non-recursive robust control design, non-recursive adaptive control design, non-recursive general dynamic predictive control, disturbance estimation and attenuation, non-recursive stability analysis, implementation theory and real-life applications to Series Elastic Actuators, DC microgrids, Permanent Magnet Synchronous Motor (PMSM) systems, etc. under the proposed non-recursive synthesis framework. This book will be a great reference for scholars and students in the field of automation and control. It will also be a useful source for control engineers and those working on anti-disturbance control, nonlinear output regulation, nonsmooth control, and other related topics"--